2017
DOI: 10.4047/jap.2017.9.5.321
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dimensions and shapes of maxillary and mandibular dental arch in Korean young adults

Abstract: PURPOSEThe aim of this study was to investigate dental arch dimensions and to classify arch shape in Korean young adults.MATERIALS AND METHODSThe sample included 50 Koreans with age ranging from 24 to 32 years. Maxillary and mandibular casts were fabricated using irreversible hydrocolloid and type III dental stones. Incisor-canine distance, incisor-1st molar distance, incisor-2nd molar distance, intercanine distance, inter-1st molar distance, and inter-2nd molar distance in both the maxillary and mandibular ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
(30 reference statements)
0
12
0
4
Order By: Relevance
“…EL overjet normal estaba presente en un 64,5%. La prevalencia de overjet aumentado fue de un 25,1%; resultado mayor que la prevalencia del overjet negativo (10,4%) [17].…”
Section: Overjet Y Overbiteunclassified
See 1 more Smart Citation
“…EL overjet normal estaba presente en un 64,5%. La prevalencia de overjet aumentado fue de un 25,1%; resultado mayor que la prevalencia del overjet negativo (10,4%) [17].…”
Section: Overjet Y Overbiteunclassified
“…Datos aproximados fueron encontrados en un estudio que determinó la prevalencia de la maloclusión de adolescentes con edades entre 12,5 y 16,2 realizado entre mayo del 2008 y diciembte de 2012 en Anatólia Central, en donde fueron estudiadas trece escuelas estatales de la cuidad de Kirikkale, localizada al sur de la capital de Turquía donde la prevalencia de los valores de mordida cruzada fue de 8,2% de la muestra [17].…”
Section: Mordida Cruzadaunclassified
“…Los estudios que utilizan el índice de Korkhaus son escasos. Aún así, al comparar la longitud transversal de las arcadas en población no caucásica es posi-ble observar diferencias: en población africana (Lombardo et al, 2015) y coreana (Park et al, 2017) se observan arcos dentarios más amplios; en Malasia, arcos más estrechos (Purmal et al, 2013); y, al comparar las medidas de los arcos en diferentes ascendencias poblacionales de un mismo país existen diferencias entre sí (Bedoya-Rodríguez et al, 2016;Alkadhi et al, 2018). Los reducidos estudios en población chilena no están aplicados en dentición permanente; se enfocan en la comparación del ancho intercanino e intermolar en dentición mixta (Vargas et al, 2013) o caracterizar la forma de las arcadas de las poblaciones autóctonas (Saavedra et al, 1987).…”
Section: Introductionunclassified
“…Many researchers have focused on the growth and development of the dental arch in adults [13]. These studies have shown that the growth and development trends of the dental arches in adults are approximately the same.…”
Section: Introductionmentioning
confidence: 99%